(untitled) (Journal of Global Accounting, 2024)
This study investigated the effect of financial leverage and market value added of listed industrial goods firms in Nigeria for a period of sixteen (16) years covering from 2008-2023. Specifically, this study ascertained the effect of debt to equity ratio, debt to asset ratio, and debt to capital ratio on market value added. Panel data were used in this study, which were obtained from the annual reports and accounts of the ten (10) sampled listed industrial goods firms for the periods 2008-2023. Ex-Post Facto research design was employed. Inferential statistics using Pearson correlation coefficient and Panel Least Square (PLS) regression analysis were applied to test the hypotheses of the study. This study revealed that debt to equity ratio has a significant but negative effect on market value added (β1 = -0.022514; P-value = 0.0154 < 0.05); debt to asset ratio has significant but negative effect on market value added (β1 = -0.288527; P-value = 0.0000 < 0.05); debt to capital ratio has significant but negative effect on market value added (β1 = -0.071215; P-value = 0.0006 < 0.05). In conclusion, the study posits that financial leverage has a significant but negative effect on market value of listed industrial goods firms in Nigeria at 5% level of significance. It was recommended amongst others that firms should lever on the amount of debt they undertake to finance their undertakings, as it enhances firms’ bottom line. Also, that firm should operate with a capital structure mix that would minimize the cost of capital and reducing the reputational risks associated with the company’s operations.